Mengukur Efektivitas Pembelajaran Pancasila dalam Membentuk Karakter Siswa di Sekolah Menengah Atas - Firdasari, Agnes; Rahmatika, Tyas; Keisha Z, Nurlalita; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
As the basis of Indonesia, Pancasila plays an important role in shaping the character and identity of citizens. The study employed a quantitative approach with a type of descriptive research by observation and interviews involving high school students. The focus of his research is on the importance of Pancasila as a moral foundation and measures students' understanding of the Pancasila values and their impact on their character. This study analyzes students' attitudes toward Pancasila learning and roles in applying Pancasila values in context of character development. Research results may provide insights into the application of the Pancasila value in learning and their impact on the character of the student, and may provide input for the development of education in other schools.